Hepatorenal syndrome: a Nationwide Trend Analysis from 2008 to 2018. (1st January 2021) - Singh, Jagmeet; Dahiya, Dushyant Singh; Kichloo, Asim; Singh, Gurdeep; Khoshbin, Katayoun; Shaka, Hafeez
Abstract: Objective: This study was designed to assess the epidemiological trends and outcomes associated with Hepatorenal Syndrome (HRS). Methods: This retrospective interrupted trend study used the Nationwide Inpatient Sample (NIS) database for the years 2008, 2012, 2014, 20z16 and 2018 to identify adult (≥18 years) hospitalizations with a primary diagnosis of HRS. We determined epidemiological characteristics and trends for HRS hospitalizations. Additionally, we also calculated the inpatient mortality, mean length of stay (LOS) and mean total hospital charge (THC) using a multivariate regression trend analysis. Results: There was an increase in the total number of HRS hospitalizations from 22, 864 in 2008 to 42, 985 in 2018 with a trend towards increasing hospitalizations ( p -trend <.001). The mean age for these hospitalizations ranged from 57.4–59.0 years with a significantly rising trend ( p -trend <.001). Although the majority of HRS hospitalizations were men, we observed a trend towards increasing hospitalizations for women with an increase from 35.7% in 2008 to 39% in 2018 ( p -trend <.001). Additionally, Whites made up a majority of the sample size (Table 1 ). After a multivariate regression trend analysis, we found a statistically significant trend towards declining inpatient mortality from 36.2% in 2008 to 25.7% in 2018 ( p -trend <.001) for HRS hospitalizations (Table 2 ). We did not find a statistically significant trend for LOS and THC. Conclusion: Total hospitalizations, hospitalizations for women and the mean age for HRS hospitalizations were on the rise between 2008 and 2018. However, the inpatient mortality declined. KEY MESSAGES: In the United States, there was a trend towards increasing hospitalizations and mean age for HRS. Although a male predominance was noted, HRS hospitalizations for women were on the rise. The inpatient mortality for HRS hospitalizations was on a decline and may indicate significant improvements in management.